Social Assistance for Poor Communities in the Perspective of Dependency Theory (A study on the community in the Winangun Dua sub-district, neighborhood 1, Manado City) - Kerebungu, Ferdinand; Pangalila, Noviska Veronika; Salem, Veronika E.T.; Mesra, Romi (Technium Social Sciences Journal, 2023)
The purpose of this study is to identify and describe the benefits and forms of social assistance provided by the state through the plaintiff’s community, which are claimed to be in accordance with the objectives of social assistance services. Data collection methods used in this study consisted of interview and observation methods. Data analysis techniques using data reduction, data display and reasoning. As a result, it was found that welfare beneficiaries in Winangun Dua Village, District 1 received welfare in the form of the Family Hope Program (PKH), Smart Indonesia Card (KIP) and Healthy Indonesia Card (KIS). The assistance provided is often used by beneficiary families to help ease the burden on the poor in dealing with their daily lives. This social assistance can improve the standard of living of beneficiary families, help the community’s economy, strengthen school spirit, and enable recipient families to open small businesses.